Analisis Pemanfaatan Beasiswa Aceh Carong Bagi Mahasiswa Politeknik Aceh - Devi Mulia Sari; Sri Rani Fauziah; Mutia Arfiani (Jurnal Ilmiah Ekonomi Terpadu (Jimetera), 2023)
The Carong Aceh Scholarship is one of the Aceh government programs to finance the education of the poor. The Aceh Carong Scholarship Program is given to prospective students who have good academic potential who are financially disadvantaged. Aceh Carong scholarship holders are exempt from tuition fees during their studies and receive a monthly allowance. The Aceh Carong Scholarship must be managed in such a way that scholarship recipients can use the Aceh Carong Scholarship to meet their daily needs. Scholarship recipients must put academic needs before individual needs and use these grants wisely. The focus of this research is the use of the Aceh Carong Scholarship for Aceh Polytechnic students. Efforts to obtain these answers were made by making research subjects using the snowball sampling method. Researchers collected information about the use of the Carong Aceh subsidy through observation, questionnaires, interviews and documentation. The results of the study show that students use their scholarships wisely and in accordance with sharia guidelines. They use scholarship funds in a simple, economical and lawful way. They are not excessive in utilizing scholarship funds. They also set aside their scholarship funds for savings. And every time they consume it, they always pay attention to its halal status